Media Development and Digital Evaluation Training to Improve High School Teacher Competence in the Industrial Revolution 4.0 Era in Sawahlunto City, Sumatera Barat - Bentri, Alwen; Hidayati, Abna (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2022)
Learning is a process of interaction between teachers and students that considers various internal and external aspects. In the internal context, the learning process needs to change regarding the industrial revolution 4.0 which has an impact on all aspects. In addition, the COVID-19 pandemic also demands many changes in the presentation of learning. Middle school teachers in Sawahlunto City have minimal knowledge about media development and digital evaluation. In connection with this, it is necessary to conduct training to increase teacher competence in the field of media and digital evaluation. The training method is online and offline with a total of 30 training participants. The training is carried out through presentations by resource persons, then practice and assistance in developing media and digital evaluations. In the final stage, training evaluation activities are carried out. Training Outcomes The trainees have competence in designing and developing digital evaluations. Regarding the process in the implementation of the training, the participants were very satisfied with the average score of the questionnaire at 4.54 (scale 1-5). The follow-up to the implementation of the training was the formation of a teacher working group and coordination through whatsApp groups to follow up on the training that had been carried out.